Microsoft Windows XP : do amazing things! - Ballew, Joli (Microsoft Press, 2004)
So let's go-it's time to have some fun and amaze yourself with all you can do with your PC! This friendly, fast-paced guide highlights dozens of activities and experiences-and shares the straightforward how-to's for trying everything out right away. So go ahead, dive in and explore the interesting, amusing, and impressive things you can do everyday with Microsoft Windows Media Player 9, Windows Movie Maker 2, Windows XP PowerToys, Plus! Digital Media Edition, and other features and tools for Windows XP! Share Your Fabulous PhotosEasily transfer photos from a digital.